Nonmonotonic potential distribution and current quenching mechanism in plasma-filled diode; Proceedings of the 17th International Symposium on Discharges and Electrical Insulation in Vacuum, ISDEIV, Berkeley, CA, july 21-26, 1996; Vol. 2 - Kondrat'eva N. P.; Korolev Y. D.; Koval N. N. Nikolay Nikolaevich; Rabotkin V. G.; Schanin P. M.; Shemyakin I. A. (1996, 1996)
The phenomenon of current quenching in a plasma filled diode forms the basis for operation of the so called plasma erosion opening switch. In typical operation conditions of the switch, a vacuum gap is preliminarily filled with a plasma from an external source after which a voltage is applied to the gap and an external electric circuit provides for a current rise with a characteristic time of the order of 1 ?s. When the current reaches some critical value the resistance of the gap sharply increases so that the current quenching and the corresponding voltage kick occurs, i.e. the gap opens for a short time. A widely used approach for interpretation of the current quenching mechanism is based on the supposition that the gap conductivity is totally determined by the plasma generated by external source. In our opinion, this viewpoint is not exactly correct, especially for the microsecond time scale, and the current passage mechanism is mainly determined by the cathode spot plasma. A foundation of this approach is presented in this paper.